Developing blog for English essay writing class - Listiani Listiani (Universitas Ahmad Dahlan)
Learning needs a medium to help learners learning. The medium can provide the learners sources of knowledge and practice. Learning English essay writing subject required its learners to understand and to have essay writing skills of English as a foreign language. The essay writing is a subject conducted by English Education Department, Faculty of teacher training and education, Universitas Muhammadiyah Purwokerto, in Central Java province in Indonesia for preparing its learners to academic writing in the next semester. Blog which can be a learning medium for learning English Essay writing was necessary to be developed for fulfilling the learners’ need. Conducting a research and development was chosen to develop the blog. This study involved 21 students in the fourth semester who took the English essay writing subject. This study took eight months from March to October 2016 in two academic years 2015/2016 and 2016/2017. Questionnaire was used to investigate students’ need on learning media; to know feedback on blog’s content, structure and navigation, and visual design from experts and students; and to find out students’ perception toward the blog developed. Documentation was also used to describe the processes of developing the blog in this research. The results showed that the blog was successfully developed regarding to the learners’ necessity for learning the subject and to the procedure passed in this research. Moreover, the blog was perceived positively (100%) to help the learners to learn the subject of English essay writing.